Contact-induced change or dialectal relic in heritage American-Danish? The indefi-nite article in copula clauses with a person-identifying subject predicate - Petersen, Jan Heegård (Norsk Lingvistisk Tidsskrift, 2018)
This article analyses the use and non-use in American Danish of the indefinite article in the identifying subject predicate construction with a bare noun as the subject predicate: hun er læge - hun er en læge 'she is a doctor'. With a point of departure in the semantics associated with use and non-use of the indefinite article in standard and dialectal Danish, the article argues that there is a clear indication of English influence with nouns denoting profession and social sta-tus. The article further discusses to what extent the use of the indefinite article with nouns that denote an inhabitant is due to influence from English or a di-alect relic. The article shows that there is a tendency for Danish immigrants in North America born in Denmark to use the Danish pattern and for descendants of immigrants to use the English pattern, but also that the pressure from English has different outcomes related to the individual speaker's inclination for using the English vs. the Danish pattern.